1989
DOI: 10.1111/j.1365-246x.1989.tb02285.x
|View full text |Cite
|
Sign up to set email alerts
|

Seismological and field observations of the 1984 Lazio-Abruzzo earthquakes: implications for the active tectonics of Italy

Abstract: Seismological and field studies of the 1984 Lazio-Abruzzo earthquakes provide new constraints on the pattern of Quaternary extension in the Apennine mountains of central Italy. Waveform modelling of the mainshock ( M , = 5.8; M, = 0.59 X 10l8 N m) at 17:49 on May 7 indicates centroid strike 123", dip 48", rake -96" and depth 10 km. The largest aftershock (M, = 5.2; M, = 0.21 X 10l8 N m), at 10:41 on May 11, had strike 170", dip 46", rake -67" and centroid depth also 10 km. The mainshock fault plane was part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(35 citation statements)
references
References 43 publications
2
32
1
Order By: Relevance
“…In addition, the best fit of the GPS velocity data is obtained considering some degree of creeping along a portion of the GuF. The mechanical behaviour of the west-dipping GuF is still debated in the literature (Boncio et al, 2000;Mirabella et al, 2004Mirabella et al, , 2008Barchi and Ciaccio, 2009 Westaway et al, 1989) that occurred in 1984 in the area (namely, the Gubbio earthquake) occurred a few kilometres apart (see location in Fig. 1a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the best fit of the GPS velocity data is obtained considering some degree of creeping along a portion of the GuF. The mechanical behaviour of the west-dipping GuF is still debated in the literature (Boncio et al, 2000;Mirabella et al, 2004Mirabella et al, , 2008Barchi and Ciaccio, 2009 Westaway et al, 1989) that occurred in 1984 in the area (namely, the Gubbio earthquake) occurred a few kilometres apart (see location in Fig. 1a).…”
Section: Discussionmentioning
confidence: 99%
“…The synthetic and antithetic structures characterized by higher dip angles compared to the ATF have generated small-moderate magnitude earthquakes; the largest one was M W 5.1 that occurred in 1984, currently called the Gubbio earthquake ( Fig. 1a; Westaway et al, 1989;Collettini e al., 2003). Several authors suggest that this seismic event, originally called the Perugia earthquake (Haessler et al, 1988), nucleated on the Gubbio fault plane (GuF; Haessler et al, 1988; while Collettini et al (2003), by interpreting a set of multidisciplinary data, argued against this hypothesis.…”
Section: The Alto Tiberina Fault Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Seismological observations on the largest earthquakes in central Italy (Anderson and Jackson, 1987;Westaway et al, 1989) have shown that active deformation is accommodated by steep planar normal faults in the upper 10-15 km of the crust as usually observed in extensional settings (Jackson and White, 1989). Below this depth, it is generally considered that the high-angle normal faults (rupturing during seismic events) assume shallower dips rooting into the ductile lower crust (Eydogan and Jackson, 1985;Rigo et al, 1996).…”
Section: Upper Crust Normal Faults Geometry and The Influence Of A Prmentioning
confidence: 99%
“…The main shock fault plane was part of the Sangro fault, one of three major SW-dipping normal faults that take up much of the extension of this part of central Italy in Lazio and Abruzzo (figure 1a) (Westaway et al, 1989). In order to evaluate the hydrological effects produced by the seismic sequence, we analyzed the data registered in 15 hydrometrical stations and the variations of levels of two lakes (Barrea and Scanno), all localised in the epicentral area and monitored by the Italian Hydrographic Survey.…”
Section: The Earthquakes Of May 1984mentioning
confidence: 99%